2018
DOI: 10.35530/it.069.02.1433
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elastane linear density on compression pressure of V-shaped compression socks

Abstract: The aim of this study was to evaluate the effect of elastane material linear densities on lateral compression values (ankle and calf) in newly designed shape (V-shape) compression socks. For this purpose, three types of yarns: main yarn (MY), plating yarn (PY) and inlaid yarn (IY) were used. Each yarn contains elastane material as core with varying linear densities. Firstly, Machine adjustments were optimized to achieve special V-shaped compression socks according to fix leg size. All the yarns were installed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, the compression pressure of CS is determined by its structure. Additionally, several studies have demonstrated a significant correlation between CS structure and compression pressure (Liu et al, 2010;Siddique et al, 2018;Zhang et al, 2019;Chen et al, 2013;Kawabata et al, 1988;Wang, 2011;Sun et al, 2020). Therefore, analyzing the structure of CS forms the basis for understanding its performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the compression pressure of CS is determined by its structure. Additionally, several studies have demonstrated a significant correlation between CS structure and compression pressure (Liu et al, 2010;Siddique et al, 2018;Zhang et al, 2019;Chen et al, 2013;Kawabata et al, 1988;Wang, 2011;Sun et al, 2020). Therefore, analyzing the structure of CS forms the basis for understanding its performance.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have demonstrated a significant correlation between CS structure and compression pressure (Liu et al. , 2010; Siddique et al. , 2018; Zhang et al ., 2019; Chen et al.…”
Section: Introductionmentioning
confidence: 99%
“…Graduated compression stockings exert pressure at a decreasing gradient from the ankle towards the thigh (Wade et al 2017). Due to this varying degree of compression pressure, the blood flow could be controlled and the muscles are kept in the correct position so patients who have chronic venous problems feel better (Siddique et al 2018). Blood flow speed is increased with the first level and second level compression stockings by 37% and 35%, respectively (Liu and Cheng 2021).…”
Section: Introductionmentioning
confidence: 99%